Managing Fragmentation of Agricultural Land for Livelihood Security in Kenya - Mugo, Fridah; Ndegwa, Elijah; Mwangi, Isaac (University of Nairobi, 2021)
Kenya’s rural population. As the population increases, per capita land available for farming reduces as more land is used for homesteads. This threatens the livelihood of those who depend on agriculture. Kenya's population has increased from 10.9 million in 1969 to 47.6 million in 2019 (KNBS, 2019). As a result, arable land per person has reduced by 71.4% from 0.42 ha. (1.04 acres) in 1961 to 0.12 ha (0.30 acres) in 2016, and the trend is continuing (World Bank, 2020). The free- hold land tenure system that allows landowners to utilize their land without user and use restriction, sub-division of land for inheritance among heirs, scattered patterns of rural settlement that rests on inefficient utilization of the land resource and unplanned agricultural production are worsening human problems from land fragmentation. Overall, these are a threat to food and livelihood security. Fragmentation of agricultural land is associated with the decline of production in the sector. This study examined the relationship between the inter-generational subdivision of agricultural land and its impacts on food and livelihood security in fifteen rural farming sub- locations covering eight counties: Kisii, Kiambu, Kirinyaga, Embu, Tranzoia, Nyandarua, Machakos and Makueni.
Keywords: Agriculture; Kenya